Bio-inspired Electrospun Fibre Structures - Numerical Model (Journal of Fiber Bioengineering and Informatics, 2013)
A systems approach that integrates processing, structure, property and performance relations hasbeen used in the design of multilevel-structured fibrous materials. For electrospun fibrous structure,numerical implementation of multiscale materials philosophy provides a hierarchy of computationalmodels defining design parameters that are integrated through computational continuum mechanics.Electrospun micro/nano (multiscale) poly(ε-caprolactone) (PCL) fibrous scaffolds were studied. Thefibrous structures were evaluated for their mechanical, morphological and cell attachment properties.The cell attachment studies showed that cell activity on multi-scale scaffolds was higher compared tomicro-fibrous scaffolds. These results suggest that the combination of a micro- and nano-fiber hierarchicalscaffold could be more beneficial for tissue engineering applications than for individual scaffolds.
Keywords: Electrospun PCL; Multiscale; Numerical Model